Evaluating the microbial effects of stocking freshwater snails (Physa gyrina) in water reuse systems culturing rainbow trout (Oncorhynchus mykiss). Issue 2 (3rd April 2019) - Davidson, John; Plautz, Carol Zygar; Grimm, Casey; Jørgensen, Niels O.G.; Podduturi, Raju; Raines, Clayton; Snader, Ryan; Summerfelt, Steven; Good, Christopher
ABSTRACT: A study was conducted to analyze the effects of snails ( Physa gyrina ) on biofilm, bacterial abundance, off-flavor-producing bacteria, and off-flavor compounds in reuse aquaculture systems culturing rainbow trout ( Oncorhynchus mykiss ). Eight experimental-scale systems were used, including four with and without snails. Mean heterotrophic bacteria counts in water were lower (P < 0.05) in systems with snails. Submerged surfaces of sumps containing snails were nearly biofilm-free, while sumps without snails were coated with biofilm. Geosmin levels in trout fillets from snail-stocked systems were generally lower but not statistically different from the controls. Rainbow trout health and performance was not affected by snail presence.